Earlier Age of Breast Cancer Onset in Israeli BRCA Carriers—Is it a Real Phenomenon?. Issue 6 (17th August 2016) - Agranat, Sivan; Baris, Hagit; Kedar, Inbal; Shochat, Mordechai; Rizel, Shulamith; Perry, Shlomit; Margel, David; Sulkes, Aaron; Yerushalmi, Rinat
Abstract: Data on genetic anticipation in breast cancer are sparse. We sought to evaluate age at diagnosis of breast cancer in daughters with a BRCA mutation and their mothers. A review of all carriers of the BRCA mutation diagnosed with breast cancer at the Genetics Institute of a tertiary medical center in 2000–2013 yielded 80 women who could be paired with a mother with breast cancer who was either a carrier of the BRCA mutation or an obligate carrier according to pedigree analysis. Age at diagnosis, type of mutation ( BRCA1, BRCA2 ), year of birth, and ethnicity were recorded. Paired t ‐test was used to analyze differences in age at cancer diagnosis between groups and subgroups. Mean age at diagnosis of breast cancer was 50.74 years (range 22–88) in the mothers and 43.85 years (range 24–75) in the daughters. The difference was statistically significant (p < 0.001). These findings were consistent regardless of type of BRCA mutation, ethnicity, or mother's year of birth. However, on separate analysis of pairs in which the mother was diagnosed before the age of 50 years, there was no significant difference in mean age at diagnosis between mothers and daughters ( 42 years for both). Daughters who carry a BRCA mutation are diagnosed with breast cancer at an earlier age than their carrier mothers, with the exception of pairs in which the mother was diagnosed before the age of 50 years. Future breast‐screening guidelines may need to target specific subpopulations of BRCA mutation carriers.